Exosomes from Tregs mitigate lung damage caused by smoking via inhibiting inflammation and altering T lymphocyte subsets in COPD rats - Xuefang Tao; Hai Tian; Guowen Wang; Yongzhen Sun; Liangyan Zhao (BMC Pulmonary Medicine)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a common disease with respiratory symptoms and limited airflow. Exosomes derived from Tregs (Treg-exo) could regulate immune function and prevent autoimmune disease. This study assessed Treg-exo effects on COPD. Methods In vivo, rats were divided into three groups including control, COPD and exosomes groups. COPD models were established by passive smoking combined with lipopolysaccharide. Phosphate buffered saline or Treg-exo were administered via tail vein. Lung function, Hematoxylin and Eosin staining, and enzyme-linked immunosorbent assay (ELISA) were performed to evaluate lung function, histopathology and inflammation. Flow cytometry was used for peripheral blood T cell separation and counting. In vitro, COPD cluster of differentiation (CD) 4+ T-cells were isolated from spleen and co-cultured with Treg-exo alone or in combination with Colivelin (a signal transducer and activator of transcription 3/STAT3 activator). Flow cytometry, ELISA, and Western blot were used to count T helper cell 17 (Th17) and detected cytokines and STAT3 proteins expression. Results In vivo, pulmonary function tests and HE staining showed Treg-exo treatment enhanced lung function and alleviated lung damage; flow cytometry showed Treg-exo treatment decreased CD8+, CD4+ CD25- cells and Th17; ELISA assay found Treg-exo treatment increased transforming growth factor-β and interleukin (IL)-10 and decreased tumor necrosis factor-α and IL-8 in serum, broncho alveolar lavage fluid, and lung tissue. In vitro, Treg-exo treatment inhibited Th17 differentiation and suppressed the content of IL-6, IL-17, and IL-23 and STAT3 phosphorylation. Conclusions Treg-exo suppressed inflammation and CD4+ T-cell differentiation to Th17, possibly by inhibiting STAT3 phosphorylation. Graphical abstract